Privatisierung und unternehmerische Probleme in Zentralasien: Ergebnisse von Unternehmensumfragen in Kasachstan, Usbekistan und Turkmenistan - Manuela Troschke; Andreas Zeitler (Osteuropa-Institut München, 2006)
This paper is presenting the results of two surveys undertaken in Kazakhstan, Uzbekistan and Turkmenistan during 2002-2004. Altogehter 136 privatized enterprises of food processing and light industries have been questioned, supplemented by qualitative interviews of selected enterprises. The overall progress in privatization of the surveyed industries as expected is in line with the respective indicator of the EBRD-Transition Index. A new, although not surprising result is the existence of a russian-style insider-privatization in Kazakhstan. A fundamentally new result is the non-existence of a chinese-style privatization in gradual reforming Uzbekistan. As in China, privatization is proceeding slowly, but in contrary to China, incentive inducing manager contracts are not widely used. Privatization in Turkemenistan reminds one of private collective enterprises coming into existence at late soviet times, who were allowed to occupy certain niches of the plan economy. The different proceeding of privatization in the three states results in differing enterprise problems. In Kazakhstan, insider privatization causes coporate governance problems like asset stripping and difficult access to credit, but restructuring is active and performance shows a strong upward trend. In Uzbekistan, enterprises in many respects still perceive support by state organs. Former line ministries, who are managing the state shares, still have control- and management rights. Hence many enterprises stay passive and show weaker performance than their counterparts of the same industry in Kazakhstan. In Turkmenistan, privatized enterprises can not compete with highlysubsidezed state enterprises and newly established joint ventures and thus stay in their niches.
Keywords: 330